2009
DOI: 10.1007/s11239-009-0432-1
|View full text |Cite
|
Sign up to set email alerts
|

The significance of genetic polymorphisms of factor V leiden and prothrombin in the preeclamptic polish women

Abstract: Many studies established that gestational hypertension (GH) and preeclampsia (PE) are multifactorial diseases and disturbances in coagulation cascade have etiological significance. Inherited thrombophilias, like polymorphism of factor V (FV) Leiden and prothrombin (PTM) are considered to be involved in the PE development. The aim of this study was to determine the association between FV Leiden and G20210A of PTM gene polymorphism and GH/PE appearance. The study comprised 235 women: GH (n = 126, mean age 27.5 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
13
0
2
Order By: Relevance
“…Also, a significantly higher prevalence of FVL mutation and its association with preeclampsia among Finnish [12] and Italian [13] women with preeclampsia have been reported. Seremak-Mrozikiewicz et al [29] in a sample of Polish preeclamptic women observed a significant association between prothrombin G20210A mutation and the development of severe preeclampsia. In another study, Prasmusinto et al [30] examined the frequency of FVL among Germans/Croatia and Indonesian and detected population differences in the association of FVL with increased risk of preeclampsia among Germans/Croatia but not in Indonesian.…”
Section: Discussionmentioning
confidence: 95%
“…Also, a significantly higher prevalence of FVL mutation and its association with preeclampsia among Finnish [12] and Italian [13] women with preeclampsia have been reported. Seremak-Mrozikiewicz et al [29] in a sample of Polish preeclamptic women observed a significant association between prothrombin G20210A mutation and the development of severe preeclampsia. In another study, Prasmusinto et al [30] examined the frequency of FVL among Germans/Croatia and Indonesian and detected population differences in the association of FVL with increased risk of preeclampsia among Germans/Croatia but not in Indonesian.…”
Section: Discussionmentioning
confidence: 95%
“…Table 1 and 2 present the results of studies that include cases of preeclampsia (not necessarily defined as severe), and Table 3 and 4 show the studies that include cases identified as severe preeclampsia. In twelve studies [15][17], [22], [25], [37][40], [48], [49], [52], only severe preeclampsia was defined and in seven[9], [10], [18], [32][35], the authors defined both preeclampsia and severe preeclampsia and performed further analysis of the association between the two polymorphisms and severe preeclampsia after analysis for all preeclampsia. In the remaining studies, the authors only defined preeclampsia and didn’t describe the distribution of mild and severe cases.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of disease definition, the criteria of the American College of Obstetricians and Gynecologists [13] and the National High Blood Pressure Education Program Working Group Report on High Blood Pressure in Pregnancy [14] were mostly used, in 13 [10], [15][26] and 6 [9], [27][31] studies, respectively, among which the definitions of preeclampsia and severe preeclampsia varied little. In these studies, preeclampsia was defined as systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg, with the presence of proteinuria by 24-h urinary excretion exceeding 300 mg after 20 weeks of gestation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is reported in an earlier twins study that heritability was 17 % for preterm delivery in first pregnancy and 27 % for preterm delivery in any pregnancy [6] and heritability range of 25%–40% was suggested for birthweight and gestational length in another study [7]. Maternal and fetal genes, either individually or in combination, could increase the risk of diseases such as hemolytic disease of the newborn [8], preterm birth [9,10], small for gestational age [11], pre-eclampsia [12-14], and preterm prelabor rupture of membranes (pPROM) [15]. The incompatibility between maternal and fetal genotypes, in which the expression of genes from two generations lead to an opposite effect, plays a vital role and can increase the risk of these diseases.…”
Section: Introductionmentioning
confidence: 99%